Three new species of the genus Pergalumna (Acari: Oribatida: Galumnidae) from India - Ermilov, Sergey G.; Shtanchaeva, Umukusum Ya.; Kalúz, Stanislav; Subías, Luis S. (Zootaxa, 2013)
Three new oribatid mite species of the genus Pergalumna (Galumnidae), P. paratsurusakii sp. nov., P. asetosa sp. nov. and P. mahunkai sp. nov., are described from India. Pergalumna paratsurusakii sp. nov. is most similar morphologically to P. tsurusakii Starý from Japan, however it differs from latter by the body surface, body size and morphology of some notogastral porose areas. Pergalumna asetosa sp. nov. is most similar morphologically to P. rotunda Starý from Japan and Pergalumna yurtaevi Ermilov & Anichkin from Vietnam, however it differs from both by the absence of interlamellar se-tae and the presence of notogastral furrows. Pergalumna mahunkai sp. nov. is most similar morphologically to P. marga-ritata Mahunka from Vietnam and P. pseudomargaritata Mahunka from Thailand, however it differs from both by the structure of anterior notogastral margin, body size and morphology of prodorsal setae.